I, spy - Kemp, L. M. (Minotaur Books, 2026)
Ex-spy Kendal was one of the best, but now she's wearing the toughest disguise of her career : Mom. Kendal Carter is out in the cold and she wouldn't have it any other way. It's been four years since her daughter Rosie was born and Kendal has kept her miles away from The Game. But when their hiding place is discovered and danger comes too close, Ken is forced to turn to old contacts. Her longtime friend and ex-handler Rico doesn't miss his chance to pull his best player back in. Whisking them to London, Rico offers them a luxury safe house in an area with good schools. How can she resist? But there's a catch, of course. Rico wants Kendal to come back to work for his espionage agency Bon Temps. He's offering a cushy assignment with no apparent downside, running a rookie asset in one of London's biggest, murkiest tech firms. It should be easy enough for someone with her experience, and luckily, mother is the perfect cover. However, it doesn't take long for Kendal to realize that Rico's got an agenda of his own. The tech firm has hands in Rosie's school, and the world of PTAs and playdates comes with its own web of allegiances and betrayals. Kendal soon finds herself in way too deep.